If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + 20 = 8u Reorder the terms: 20 + 3u = 8u Solving 20 + 3u = 8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-8u' to each side of the equation. 20 + 3u + -8u = 8u + -8u Combine like terms: 3u + -8u = -5u 20 + -5u = 8u + -8u Combine like terms: 8u + -8u = 0 20 + -5u = 0 Add '-20' to each side of the equation. 20 + -20 + -5u = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -5u = 0 + -20 -5u = 0 + -20 Combine like terms: 0 + -20 = -20 -5u = -20 Divide each side by '-5'. u = 4 Simplifying u = 4
| 6x+13=-9-10 | | 7g-15=g-3 | | 2x+x^2+144=0 | | 85-3x=2x+10 | | (4-2k+3l)+(2-3k-2l)= | | 135-2x=34x+15 | | -104-7x=10x+15 | | 2x+12=-38-8x | | y=-32x^2-6x | | y=-32x^2-6x | | y=-32x^2-6x | | 2x^2+30=0 | | 14-10x=74-24x | | -37-7x=7x+20 | | (7z-3)-(4z-11)=47 | | 6t-5=2t-5 | | 266-6x=39x+21 | | 3r+6=18 | | 7x(-2x+3)=0 | | 6x(4x+3)=0 | | 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x |